2015
DOI: 10.3390/s150717507
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fear Using Nonintrusive Measurement of Multimodal Sensors

Abstract: Most previous research into emotion recognition used either a single modality or multiple modalities of physiological signal. However, the former method allows for limited enhancement of accuracy, and the latter has the disadvantages that its performance can be affected by head or body movements. Further, the latter causes inconvenience to the user due to the sensors attached to the body. Among various emotions, the accurate evaluation of fear is crucial in many applications, such as criminal psychology, intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…However, only certain types of emotions can be recognized using EEG. Moreover, finding key emotional states to be recognized is mandatory; for example, six emotions were detected in [42,45,106,120,122,192], whereas in [108], a real-time EEG signal to classify happy and unhappy emotions was proposed, and in [113], a fear evaluation system was proposed. In our review, we found that most of the articles aim to detect unpleasant, pleasant, and neutral emotions, such as in [105,217], or positive, negative, and neutral emotions that are based on the valence-arousal dimensional emotion model, as in [159,206].…”
Section: Eeg Correlates Of Emotion (Signals)mentioning
confidence: 99%
“…However, only certain types of emotions can be recognized using EEG. Moreover, finding key emotional states to be recognized is mandatory; for example, six emotions were detected in [42,45,106,120,122,192], whereas in [108], a real-time EEG signal to classify happy and unhappy emotions was proposed, and in [113], a fear evaluation system was proposed. In our review, we found that most of the articles aim to detect unpleasant, pleasant, and neutral emotions, such as in [105,217], or positive, negative, and neutral emotions that are based on the valence-arousal dimensional emotion model, as in [159,206].…”
Section: Eeg Correlates Of Emotion (Signals)mentioning
confidence: 99%
“…In addition, as shown in Table 10, the proposed method in this study was more accurate than the existing method [21], which uses SE, FT, and EBR individually. The existing study [27] also showed results where the average correlation values decrease in the following order: FT, SE, and EBR. The results derived from Table 10 indicate the same order, showing consistency with the existing study results.…”
Section: Experimental Results and Analysesmentioning
confidence: 91%
“…In addition, visible light cameras are jointly used with thermal cameras to identify facial feature points with correlations of changes in location of the two groups of cameras, studied through prior calibration. Based on the data obtained from this calibration, coordinates of the location of facial feature points identified through visible light cameras were mapped onto the images obtained by thermal cameras to identify the facial feature points in them [27].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, except for statistics-based features in time domain [12], energy-based and entropy-based features of EEG have gradually been applied a lot for human emotion recognition. Choi et al [13] used power change of the ratio of delta (δ) to beta (β) waves of EEG before and after watching scary film chips to conduct fear evaluation. Schaaff et al [14] recognized three different emotions including pleasant, neutral, and unpleasant by support vector machine (SVM), based on EEG characteristics such as peak alpha (α) frequency and α power.…”
Section: Introductionmentioning
confidence: 99%